2020
DOI: 10.1200/jco.19.01180
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Disease After Male Germ Cell Cancer

Abstract: PURPOSE To analyze the risk of cardiovascular disease (CVD) after treatment of male germ cell cancer (GCC). METHODS Clinical data were extracted from the Danish Testicular Cancer database. For each patient, 10 men matched on date of birth were identified in the Danish normal population by risk-set sampling. Cardiovascular risk factors, CVD, and associated deaths were identified in Danish registries. The association between treatment and outcomes was analyzed by separate Cox models for each outcome. Cancer trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 34 publications
4
41
1
3
Order By: Relevance
“…The over-all cure rate is more than 90 % and most of the patients with GCT will enjoy a long life-expectancy despite the diagnosis of cancer [ 2 ]. Therefore, physicians caring for GCT patients are increasingly looking for long-term consequences of treatment, mainly second malignant neoplasms, cardiovascular disease and endocrinological disorders [ 3 5 ]. Recently, dysregulation of the vitamin D metabolism secondary to cancer-related loss of one testicle has come into the focus [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The over-all cure rate is more than 90 % and most of the patients with GCT will enjoy a long life-expectancy despite the diagnosis of cancer [ 2 ]. Therefore, physicians caring for GCT patients are increasingly looking for long-term consequences of treatment, mainly second malignant neoplasms, cardiovascular disease and endocrinological disorders [ 3 5 ]. Recently, dysregulation of the vitamin D metabolism secondary to cancer-related loss of one testicle has come into the focus [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of myocardial infarction (hazard ratio (HR): 6.3 (95% CI: 2.9-13.9)), cerebrovascular morbidity (HR: 6.0 (95% CI: 2.6-14.1)), and venous thromboembolism (HR 24.7 (95% CI: 14.0-43.6)) was identified in patients shortly after treatment with cisplatinbased chemotherapy. Although it decreased to levels of the general population within one year after treatment, the risk of myocardial infarction and cardiovascular disease-related death increased again 10 years after treatment-HR: 1.4 (CI: 1.0-2.0) and HR: 1.6 (CI: 1.0-2.5), respectively [40]. Other works show a 1.5-to 5.7-fold increase in the risk of cardiovascular disease in patients treated with chemotherapy compared to those treated with orchiectomy only [41][42][43].…”
Section: Treatment-induced Cardiovascular Toxicity and Neurocognitivementioning
confidence: 89%
“…NCT01069081). For example, a recent study presented at the 2020 American Society of Clinical Oncology (ASCO) reported that administration of PPIs with chemotherapy to triple-negative breast cancer (TNBC) patients was associated with significant pathologic complete response (pCR) rate without adding toxicity (clinical trial # NCT02595372) [ 47 ]. Although the doses of PPI required to achieve plasma concentration of about 100 μM for radiosensitizing activity is higher than the standard antacid dose, it is safely achievable in cancer patients.…”
Section: Discussionmentioning
confidence: 99%